Аеродинамічне дослідження вісерадіальних дифузорів для осьового компресора газотурбінної установки - Юдін, Юрій Олексійович; Суботович, Валерій Петрович; Лапузін, Олександр Вікторович; Малимон, Іван Іванович (Національний технічний університет "Харківський політехнічний інститут", 2019)
Виконано розрахункове дослідження аеродинаміки п'яти варіантів вихідних вісерадіальних дифузорів осьового компресору газотурбінної установки ГТ-6-750. Дослідження проведене в широкому діапазоні кутів входу в дифузор компресора зі зміною форми обтічника в кожному варіанті. Розрахунки виконані у програмному комплексі Fluent. За результатами дослідження можна рекомендувати встановити модернізований варіант дифузору і відмовитись від випрямних апаратів для зменшення коефіцієнтів втрат, відривних явищ і зворотних течій.

The objectives of research done were to define the geometric characteristics of the fairing of axial-radial diffuser that provide the lowest overall loss coefficient (the sum of the coefficients of internal losses and output velocity losses) and evaluate the possibility for the non-use of straightening grids behind the rotor of the last stage of compressor. Using the CFD program we conducted the calculated analysis of aerodynamic characteristics for the five options of outlet axial-radial diffusers used for the axial compressor of the gas turbine plant GT-6-750. The flow for all five options of the diffuser was calculated for preset constant total pressure and total temperature at the channel input and the static pressure at the diffuser output. The angles of incidence of the flow into the channel were varied in a wide range of the values for all the options of the diffuser. A comparative analysis of the aerodynamic characteristics of the diffusers was performed and the values of the coefficients of total losses, internal losses and output velocity losses were defined. A version of the stage by-pass was suggested for the diffuser that provides the lowest coefficient of total losses in the entire range of a change in the angles of flow incidence. The diffuser of this type has a considerably reduced intensity of separation phenomena in the input axial circular channel section and in the radial channel section. For the diffusers of this type with a short input axial section and substantial radiality a conclusion was drawn up that the use of straightening grids after the rotor of the last stage of compressor is inexpedient.
Aerodynamic investigation of axial-radial diffusers for axial compressor of gas turbine plant
Keywords: випрямний апарат; коефіцієнт втрат; кут потоку; обтічник; straightener blade; loss factor; flow angle; fairing